ANALISIS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SDN 071167 HILIBANUA - FERDY SETIAWAN LAHAGU; EKA SEPTIANTI LAOLI; NETTI KARIANI MENDOFA (JURNAL ILMIAH SIMANTEK, 2022)
The purpose of this study was to analyze how management and School Operational Assistance at SDN 071167 Hilibanua have implemented management methods in a transparent, accountable, effective and efficient manner. The research method used is a qualitative type of approach, namely solving research problems by describing the conditions of the SDN 071167 Hilibanua school in managing School Operational Assistance funds based on actual facts in the field, using interview, observation, and documentation methods. The results of the research are the management of Operational Assistance funds Schools at SDN 071167 Hilibanua have implemented management methods in a transparent, accountable, effective and efficient manner.